Efecto de la utilización de harina de zanahoria (Daucus carota) y alfarina (Medicago sativa) en la pigmentación y características organolépticas de la carne de pollo broiler. - Miniguano Valle, Víctor Jacobo (2020)
The development of the present investigation called "effect of the use of carrot (Daucus carota) and alfarina (Medicago sativa) flour in the pigmentation and organoleptic characteristics of broiler chicken meat", in the Amaguaña parish in the city of Quito. Using the appropriate materials to determine the birds' fattening with different study treatments using 5 to 10% of carrot and alfarina flour, balanced vitamins, and injection of vaccines to prevent diseases in 63 days for fattening for the evaluation of pigmentation and organoleptic characteristics through qualitative scales. Determining the fattening weights in each one of the treatments. High values were obtained using 10% of alfarina flour with a final gain of 2699.15 g, and as a final result, the weight to the carcass was 2121.41 g with a final yield of 78.6% being the best method to increase the weight of the chickens. When evaluating the pigmenting and organoleptic characteristics, they favored the treatment of 4 getting regular meat, with pleasing odor and metallic flavor. Besides, when estimating the economic income and expenses that can be generated in each study methodology, reliable results were obtained by assigning to treatments 4 and 0 those that create the most significant amount of benefits, but the use of 10 % of alfarina flour generating net profits of 0.26 USD for each dollar. At the end of the study, it was concluded that balanced and 10% of alfarina flour allows us to obtain excellent weight gains, organoleptic characteristics, pigmentation, and economic benefits.